Cultural politics-- queer reading - Sinfield, Alan (Routledge, 2005)
Sinfield presents a bold & enduring challenge to assumptions that have shaped the study of English literature. He offers a widely influential investigation of the principles & practice that may inform dissident reading & a compelling argument for intellectual allegiances beyond the academy.